Sustainability-Driven Consumer Experience Design of an Online Retail System for Household Appliances - Lu, Yichen; Yan, Tian (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: In the field of information system design, mobile-based platforms have emerged as a significant and indispensable component in recent years. This research examines the incorporation of sustainable responsibility by a household appliance brand into the consumer experience of a retail mobile application through experience design.OBJECTIVES: The primary objective of this study is to develop strategies for consumer experience design driven by sustainability, thereby fostering the adoption of sustainable consumption behaviours that yield positive implications for the environment, public life, and brand values.METHODS: A combination of quantitative and qualitative methods was employed, encompassing preliminary user interviews, questionnaire surveys, and in-depth user interviews. Initially, design research explored consumers' comprehension of sustainability, sustainable consumption demands, behavioural habits, and experiential expectations. Subsequently, design strategies were derived through insight clustering analysis, considering functional information, interaction experience, and marketing interaction.RESULTS: The study illustrated sustainable consumer experience design through the interface and interaction design of a retail mobile application, serving as a touchpoint for an online retail system. The overall effectiveness of the design solution was assessed through usability and consumer experience tests and the results were positive and evidently conducive to improve the retail mobile application.CONCLUSION: Based on the evaluation of the design proposal, three key elements were identified for the experience design of retail mobile systems driven by sustainable responsibility: accentuating the sustainable attributes of products, enhancing consumer autonomy and competence, and aligning marketing endeavours with sustainable values.
Keywords: sustainable responsibility; brand of household appliances; retail mobile application; consumer experience design; household appliances